Classification of Organic Coffee Consumers Based on Typology of Environmental Strategies with Cluster Analysis - Wati Susilawati (Fakultas Ekonomi Universitas Garut, 2023)
In recent years, there has been a growing interest in organic farming among the public, driven by the desire for healthy and environmentally-friendly consumption. Currently, the consumption of organic products has increased in almost all regions and has even spread to countries that were initially only producers and suppliers for Western countries. Indonesia is one of the countries that has recently shown interest in organic products. The aim of this research is to identify consumers of organic coffee products by conducting cluster analysis on a sample of 400 consumers. The results indicate that there are two classifications among the four groups of consumers, namely those belonging to the vocal green consumers, silent green consumers, vocal brown consumers, and silent brown consumers.